# Solve for d (d-5)(d+5)=39

(d-5)(d+5)=39
Simplify (d-5)(d+5).
Expand (d-5)(d+5) using the FOIL Method.
Apply the distributive property.
d(d+5)-5(d+5)=39
Apply the distributive property.
d⋅d+d⋅5-5(d+5)=39
Apply the distributive property.
d⋅d+d⋅5-5d-5⋅5=39
d⋅d+d⋅5-5d-5⋅5=39
Simplify terms.
Combine the opposite terms in d⋅d+d⋅5-5d-5⋅5.
Reorder the factors in the terms d⋅5 and -5d.
d⋅d+5d-5d-5⋅5=39
Subtract 5d from 5d.
d⋅d+0-5⋅5=39
d⋅d-5⋅5=39
d⋅d-5⋅5=39
Simplify each term.
Multiply d by d.
d2-5⋅5=39
Multiply -5 by 5.
d2-25=39
d2-25=39
d2-25=39
d2-25=39
Move all terms not containing d to the right side of the equation.
Add 25 to both sides of the equation.
d2=39+25
d2=64
d2=64
Take the square root of both sides of the equation to eliminate the exponent on the left side.
d=±64
The complete solution is the result of both the positive and negative portions of the solution.
Simplify the right side of the equation.
Rewrite 64 as 82.
d=±82
Pull terms out from under the radical, assuming positive real numbers.
d=±8
d=±8
The complete solution is the result of both the positive and negative portions of the solution.
First, use the positive value of the ± to find the first solution.
d=8
Next, use the negative value of the ± to find the second solution.
d=-8
The complete solution is the result of both the positive and negative portions of the solution.
d=8,-8
d=8,-8
d=8,-8
Solve for d (d-5)(d+5)=39

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top